Consumer attitudes toward information displayed at food buffets in commercial restaurants - Tatiana Barbieri; Karina de Souza Rodrigues; Simone Ferreira da Silva; Laissa Benites Medeiros; Ana Lúcia de Freitas Saccol (2012)
This study aimed to evaluate the attitude of consumers towards information about dishes in a commercial restaurant. This research was conducted from January to April 2009 in a restaurant in the city of Santa Maria (RS), Brazil. Food information including the name of the dish, ingredients, health benefits and warnings, and calorie value was displayed. After providing this nutritional information, a questionnaire was applied to 300 consumers at the restaurant to observe their attitudes towards the food information. It was found that 10.57% of the respondents reported allergy or intolerance to some kinds of food and that 10.98% of the respondents reported having diseases that require moderate consumption and/or total restriction on the consumption of those foods. However, 84.96% of the respondents did not restrict consumption of any food, even though those foods may have posed a risk to their health, and 58.54% of the respondents consumed some food due to the potential benefits to their health. With regard to the respondents' level of satisfaction concerning the food information provided, 72.76% considered the information provided as very good. The respondents had a tendency to change their behavior towards consumption after having access to information about the dishes displayed.